2017
DOI: 10.1016/j.neuro.2017.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Reduced expression of PARK2 in manganese-exposed smelting workers

Abstract: Manganese (Mn) is widely used in modern industries. Occupational exposure to Mn is known to cause clinical syndromes similar, but not identical to, Parkinson’s disease. This human cohort study was designed to investigate if workers exposed to Mn altered the PARK2 gene expression, leading to Mn-induced neurotoxicity. Workers (n = 26) occupationally exposed to Mn were recruited from a Mn-iron (Fe) alloy smelter, and control workers (n = 20) without Mn-exposure were from an Fe smelter from Zunyi City in China. Su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 41 publications
1
11
0
Order By: Relevance
“…In a Canadian cohort of school-age children consuming well water, water Mn was weakly correlated with Mn in saliva supernatant (r=0.14), although strong correlations (r=0.60) were reported between water and hair Mn in the same subjects (68). In occupational settings, however, stronger positive correlations were reported for saliva Mn with airborne Mn (r=0.65), as well as with length of employment, plasma Mn, and red blood cell Mn (56, 65–67), suggesting saliva Mn reasonably reflects Mn levels in the air and/or work environment. Heterogeneity in findings between studies regarding the utility of saliva as a biomarker may be explained in part by different analytical methods for processing and measuring saliva Mn, as well as by differences in the type of saliva collected, because saliva is secreted by the parotid, submandibular, and sublingual glands (69).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In a Canadian cohort of school-age children consuming well water, water Mn was weakly correlated with Mn in saliva supernatant (r=0.14), although strong correlations (r=0.60) were reported between water and hair Mn in the same subjects (68). In occupational settings, however, stronger positive correlations were reported for saliva Mn with airborne Mn (r=0.65), as well as with length of employment, plasma Mn, and red blood cell Mn (56, 65–67), suggesting saliva Mn reasonably reflects Mn levels in the air and/or work environment. Heterogeneity in findings between studies regarding the utility of saliva as a biomarker may be explained in part by different analytical methods for processing and measuring saliva Mn, as well as by differences in the type of saliva collected, because saliva is secreted by the parotid, submandibular, and sublingual glands (69).…”
Section: Discussionmentioning
confidence: 96%
“…Saliva is promising as a noninvasive sample, but relatively little is known about its utility as a biomarker of Mn exposure. Weak to modest correlations between saliva Mn and other Mn measures have been reported in both environmental and occupational exposure studies (56, 65–67). In a Canadian cohort of school-age children consuming well water, water Mn was weakly correlated with Mn in saliva supernatant (r=0.14), although strong correlations (r=0.60) were reported between water and hair Mn in the same subjects (68).…”
Section: Discussionmentioning
confidence: 98%
“…2008 ). Among Mn-exposed welders, studies investigating saliva Mn have reported significant correlations with serum Mn ( ), airborne Mn ( ), and years of work experience ( ) ( Fan et al. 2017 ; Wang et al.…”
Section: Discussionmentioning
confidence: 99%
“…Although research using saliva as a biomarker for Mn exposure is sparse, recent studies describing analytical methodologies for measuring saliva Mn in humans have reported associations between environmental Mn exposure and saliva Mn levels (Butler et al 2019;Lucas et al 2015) and have quantified saliva Mn in occupationally exposed workers (Gil et al 2011;Wang et al 2008). Among Mn-exposed welders, studies investigating saliva Mn have reported significant correlations with serum Mn (r = 0:57), airborne Mn (r = 0:65), and years of work experience (r = 0:40) (Fan et al 2017;Wang et al 2008;Zhou et al 2010). In environmental studies of children, saliva Mn was significantly associated with air and soil Mn in areas near ferroalloy activity in the same cohort as the present study (Butler et al 2019), but not with Mn in drinking water in a Canadian cohort (Bouchard et al 2018;Ntihabose et al 2018).…”
Section: Environmental Health Perspectivesmentioning
confidence: 99%
“…Occupational Mn exposure occurs in Zunyi, China. In collaboration with Purdue University, we have conducted studies of Mn smelter workers on early behavioral changes and biomarkers, and identified the blood Mn/Fe ratio as a novel biomarker of Mn exposure [9,10], we have discovered the association of divalent metal transporter-1, transferrin and hepcidin in blood and Mn exposures [12], and demonstrated reduced PARK2 expression in Mn smelter workers [13]. A transportable in vivo neutron activation analysis system was designed and utilized to assess bone Mn as accumulative Mn exposure, and found bone Mn and fingurenail Mn are associated with cognitive dysfunction in Mn-exposed workers [36,37].…”
Section: Introductionmentioning
confidence: 99%